Victimización, polivictimización e ideación suicida en jóvenes de Matamoros durante la pandemia por Covid-19, un estudio exploratorio - Alejandro Martínez Hernández, Karla Villarreal Sotelo, Fabiola Peña Cárdenas & Carolina Landero Pérez (Facultad de Trabajo Social y Desarrollo Humano, 2022)
Suicide is a complex phenomenon that results in a Public Health problem. A large number of authors have joined the generation of knowledge around mental health, especially about suicidal ideation during the period of the pandemic. Drastic changes in lifestyle and confinement could be a triggering factor for the exacerbation of violence in different contexts, and mental health that can affect adolescents and young people. This research analyzes the victimization, polyvictimization and suicidal ideation in adolescents and young people from Matamoros during the period of COVID-19. For this purpose, a survey was designed in Google forms that was disseminated and applied during the period from February to March 2021. The sample consists of 93 adolescents and young people from Matamoros, Tamaulipas selected by a non-probabilistic sampling for snowball convenience, being 53.8% women, and 41.9% men. It was found that of the surveyed population four fifths (80.6%), has remained in confinement, and 80.6% has had an acquaintance who has suffered contagion by COVID-19, 46.2% has an acquaintance who has died a victim of COVID-19, 23.7% of the participants have been infected with COVID-19. Finding a significant association with respect to sex, being higher the probability of staying in confinement in men with 33.3% in contrast to 16% of women. 45.2% of participant’s report thoughts about death during the COVID-19 period, and in the same proportion report having had them at other times in their lives. While 36.6% have wished they were dead and 40.2% have wanted it at other times in their lives. In the comparison by sex of suicidal ideation in men and women, significant associations were found with respect to sex, being more likely to present them in women in contrast to men. 56% of women against 33.3% of men reported ideas about death during confinement. 48% of the female sex over 28.2% by the male sex, indicated suicidal ideation before the confinement by COVID-19. The percentages also doubled in the case of death wishes both during and before confinement for women. The results show the importance of mental health during the pandemic, especially taking data from the present study for the implementation of preventive actions in at-risk populations such as women and those with previous suicidal ideation.